In vivo gene transfer to the mouse nasal cavity mucosa using a stable cationic lipid emulsion - Kim, TW; Chung, H; Kwon, IC; Sung, HC; Jeong, SY (SPRINGER-VERLAG SINGAPORE PTE LTD, 2000)
We evaluate a new cationic emulsion as a mucosal gene carrier and elucidate the relationship between the transfection efficiency and the stability of the carrier/DNA complex. A cationic lipid emulsion was formulated with soybean oil and 1,2-dioleoyl-sn-glycero-3-trimethylammonium-propane (DOTAP) as major components and was used to transfer genes to the epithelial cells of the mouse nasal cavity tia intranasal instillation, Correlation between the transfection efficiency and the stability of the carrier/DNA complex was investigated by measuring the carrier size changes and by observing the degree of DNA protection against DNase I digestion in the presence of heparin, The cationic emulsion showed at least 3 times better transfection activity than the liposomal carriers in nasal mucosae, The cationic emulsion was stable in the presence of heparin whereas the liposomal carriers became very unstable. Unlike DNA in tiposome/DNA complexes, DNA in the emulsion/DNA complex was resistant to heparin exchange and DNase I digestion. The cationic emulsion was more effective in delivering DNA to nasal mucosae than commercially available liposomal carriers, The transfection activities of the lipid carriers in nasal cavity mucosae are in agreement with the stability of the lipid carriers and their complexes with DNA.
Keywords: CYSTIC-FIBROSIS; DNA; COMPLEXES; FORMULATIONS; THERAPY; CELLS; MICE